The Influence of Social Value Orientation, Community Engagement, and Innovation Agility on Social Based Organization Growth in Indonesia - Sihite, Mislan; Sumantri, Bambang Agus (International Journal of Business, Law, and Education, 2025)
This study investigates the influence of Social Value Orientation, Community Engagement, and Innovation Agility on the growth of Social-Based Organizations (SBOs) in Indonesia. Using a quantitative, explanatory research design, data were collected from 185 organizational leaders representing various SBOs across multiple sectors. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that all three constructs have a significant and positive impact on organizational growth. Community Engagement emerged as the most influential factor, highlighting the importance of participatory practices and stakeholder involvement in program success and sustainability. Social Value Orientation was also found to play a vital role by reinforcing ethical decision-making and prosocial behavior, which enhance trust and long-term legitimacy. Innovation Agility contributes to growth by enabling organizations to respond adaptively to changing societal needs. These findings suggest that a synergistic combination of internal values, community collaboration, and adaptive capabilities is essential for driving sustainable growth in SBOs. The study contributes to the literature on social enterprise development and offers practical insights for strengthening organizational strategy in the nonprofit sector.